Evaluación técnico-financiera de la inyección tipo WAG con flue gas proveniente de la refinería de Barrancabermeja en las arenas B de la formación mugrosa en un campo mediante una simulación numérica (2019)
The main objective of this research work is to study a possible case of alternating injection of water and Flue Gas from the Barrancabermeja refinery in an oil field located in the middle Magdalena Valley basin, more Specifically in the arenas B of the filthy formation and through this, stipulate if the project of improved oil recovery is viable economically for the company Ecopetrol, S.A.